Photochemical Evolution of the 2013 California Rim Fire: Synergistic Impacts of Reactive Hydrocarbons and Enhanced Oxidants - Wolfe, Glenn; Hanisco, Thomas F.; Arkinson, Heather L.; Blake, Donald R.; Clair, Jason St.; et al (Copernicus Publications, 2022)
Large wildfires markedly alter regional atmospheric composition, but chemical complexity challenges model predictions of downwind impacts. Here, we elucidate key facets of gas-phase photochemistry and assess novel chemical processes via a case study of the 2013 California Rim Fire plume. Airborne in situ observations, acquired during the NASA Studies of Emissions, Atmospheric Composition, Clouds and Climate Coupling by Regional Surveys (SEAC4RS) mission, illustrate the evolution of volatile organic compounds (VOC), oxidants, and reactive nitrogen over 12 hours of atmospheric aging. Measurements show rapid formation of ozone and peroxyacyl nitrates (PNs), sustained peroxide production, and prolonged enhancements in oxygenated VOC and nitrogen oxides (NOₓ). Measurements and Lagrangian trajectories constrain a 0-D puff model that approximates plume photochemical history and provides a framework for evaluating key processes. Simulations examine the effects of 1) previously-unmeasured reactive VOC identified in recent laboratory studies, and 2) emissions and secondary production of nitrous acid (HONO). Inclusion of estimated unmeasured VOC leads to a 250 % increase in OH reactivity and a 70 % increase in radical production via oxygenated VOC photolysis. HONO amplifies radical cycling and serves as a downwind NOₓ source, although two different HONO production mechanisms (particulate nitrate photolysis and heterogeneous NO₂ conversion) exhibit markedly different effects on ozone, NOₓ, and PNs. Analysis of radical initiation rates suggests that oxygenated VOC photolysis is a major radical source, exceeding HONO photolysis when averaged over the first 2 hours of aging. Ozone production chemistry transitions from VOC-sensitive to NOₓ-sensitive within the first hour of plume aging, with both peroxide and organic nitrate formation contributing significantly to radical termination. To simulate smoke plume chemistry accurately, models should simultaneously account for the full reactive VOC pool and all relevant oxidant sources.
Authors: Glenn M. Wolfe, Thomas F. Hanisco, Heather L. Arkinson, Donald R. Blake, Armin Wisthaler, Tomas Mikoviny, Thomas B. Ryerson, Ilana Pollack, Jeff Peischl, Paul O. Wennberg, John D. Crounse, Jason M. St. Clair, Alex Teng, L. Gregory Huey, Xiaoxi Liu, Alan Fried, Petter Weibring, Dirk Richter, James Walega, Samuel R. Hall, Kirk Ullmann, Jose L. Jimenez, Pedro Campuzano-Jost, T. Paul Bui, Glenn Diskin, James R. Podolske, Glen Sachse, and Ronald C. Cohen